De main en main / de mano a mano — essai de classement et de traitement didactique des unités figées se référant au lexème main en français et mano en espagnol en vue de l’enseignement de la phraséologie à des locuteurs non-natifs - Żłobińska-Nowak, Aleksandra (Neophilologica, 2016)
The present paper is intended to analyze the most frequent phraseological units containing the French productive lexem main and the Spanish lexem mano. The first part of the paper revolves around the most important basic structures of the phraseological units with selected nouns, as well as all types of grammatical categories of which those structures are composed. Then, the Author proposes several exercises devoted to support the natural acquisition of the presented expressions. The aim of the paper is also to show the utility of phraseodidactics, or didactics of phraseology, as a new field of applied linguistics and its domain phraseology. The author stresses the importance of the development of phraseological competences in the process of foreign languages didactics and the need to develop methods of teaching and learning phraseological units such as idioms, proverbs, in the second and additional language(s).